Universality and Halo Nuclei - Tomio, Lauro [UNESP] (E D P Sciences, 2009)
Universal aspects of few-body systems will be reviewed motivated by recent interest in atomic and nuclear physics. The critical conditions for the existence of excited states in three-body systems with two-identical particles will be explored. In particular, we consider halo nuclei that can be modeled as three-body nuclear systems, with two halo neutrons and a core. In this context, we also discuss the low-energy neutron-C-19 elastic scattering, near the conditions for the appearance of an Efimov state.